Chemotherapy-induced antitumor immunity requires formyl peptide receptor 1 - Vacchelli, Erika; Ma, Yuting; Baracco, Elisa E; Sistigu, Antonella; Enot, David P; Pietrocola, Federico; Yang, Heng; Adjemian, Sandy; Chaba, Kariman; Semeraro, Michaela; Signore, Michele; De Ninno, Adele; et al. (Science (New York, N.Y.), 2015)
Antitumor immunity driven by intratumoral dendritic cells contributes to the efficacy of anthracycline-based chemotherapy in cancer. We identified a loss-of-function allele of the gene coding for formyl peptide receptor 1 (FPR1) that was associated with poor metastasis-free and overall survival in breast and colorectal cancer patients receiving adjuvant chemotherapy. The therapeutic effects of anthracyclines were abrogated in tumor-bearing Fpr1(-/-) mice due to impaired antitumor immunity. Fpr1-deficient dendritic cells failed to approach dying cancer cells and, as a result, could not elicit antitumor T cell immunity. Experiments performed in a microfluidic device confirmed that FPR1 and its ligand, annexin-1, promoted stable interactions between dying cancer cells and human or murine leukocytes. Altogether, these results highlight the importance of FPR1 in chemotherapy-induced anticancer immune responses.
Keywords: přirozená imunita; kolorektální nádory; Neoplasms; Anthracyclines; Cell Line, Tumor; Chemotherapy, Adjuvant; Receptors, Formyl Peptide; annexin A1; nádory prsu; jednonukleotidový polymorfismus; dendritické buňky; T-lymfocyty; Immunity, Innate; leukocyty; Animals; Polymorphism, Single Nucleotide; lidé; Annexin A1; ženské pohlaví; Breast Neoplasms; Humans; zvířata; Leukocytes; myši; Colorectal Neoplasms; antracykliny; adjuvantní chemoterapie; nádory; receptory pro formylované peptidy; T-Lymphocytes; Alleles; nádorové buněčné linie; Dendritic Cells; Female; Mice; alely